Advances in epigenetic mechanisms of chick embryo heat acclimation - Xu, Peng; Lin, Hai; Jiao, Hongchao; Zhao, Jingpeng; Wang, Xiaojuan (World's poultry science journal, 2022)
SUMMARYThe environment is closely related to the healthy rearing of animals. As an environmental stressor, heat stress has been paid close attention by practitioners. The high-temperature environment in summer will cause serious damage to poultry health and economic loss. As global temperatures rise, there is an urgent need for ways to mitigate heat stress damage in poultry. Studies have found that heat acclimation techniques can help poultry improve their resistance to high temperatures. Epigenetics is a subject closely related to the environment. Epigenetic changes of related genes may play an important role in the establishment of heat acclimation. In this article, we summarise the existing reports on heat acclimation techniques and try to explore them from the perspective of epigenetics.